The burden of severe hypertensive disorders of pregnancy on perinatal outcomes: a nationwide case-control study in SurinameAJOG Global Reports at a Glance - Zita D. Prüst, MD; Lachmi R. Kodan, MD, PhD, MSc; Thomas van den Akker, MD, PhD; Kitty W.M. Bloemenkamp, MD, PhD; Marcus J. Rijken, MD, PhD; Kim J.C. Verschueren, MD, PhD (Elsevier, 2021)
BACKGROUND: Latin America and the Caribbean is the region with the highest prevalence of hypertensive disorders of pregnancy worldwide. In Suriname, where the stillbirth rate is the second highest in the region, it is not yet known which maternal factors contribute most substantially. OBJECTIVE: The aims of this study in Suriname were to (1) study the impact of different types of maternal morbidity on adverse perinatal outcomes and (2) study perinatal birth outcomes among women with severe hypertensive disorders of pregnancy. STUDY DESIGN: A case-control study was conducted between March 2017 and February 2018 during which time all hospital births (86% of total) in Suriname were included. We identified babies with adverse perinatal outcomes (perinatal death or neonatal near miss) and women with severe maternal morbidity (according to the World Health Organization Near Miss tool). Stillbirths and early neonatal deaths (<7 days) were considered perinatal death. We defined a neonatal near miss as a birthweight below 1750 g, gestational age <33 weeks, 5-minute Apgar score <7, and preterm intrauterine growth restriction <p3. Descriptive statistics and multivariate binary logistic regression analyses were conducted. RESULTS: In the 1-year study period, adverse perinatal outcomes were reported for 638 singleton births of which 120 (18.8%) involved women with severe maternal morbidity. In most of these cases, the mother suffered severe hypertensive disorders of pregnancy (n=95/120, 79.2%). Severe hypertensive disorders of pregnancy were strongly associated with adverse perinatal outcomes (adjusted odds ratio, 11.1; 95% confidence interval, 8.3-14.9). The prevalence of severe hypertensive disorders of pregnancy in Suriname was 2.5% (234/9197). Of the 215 singleton pregnancies complicated by severe hypertensive disorders, adverse perinatal outcomes were reported for 44.2% of them (n=95/215; adjusted odds ratio, 11.1; 95% confidence interval, 8.3-14.9); perinatal death accounted for 18.1% of these cases (n=39/215; adjusted odds ratio, 8.6; 95% confidence interval, 5.8-12.7) and neonatal near miss accounted for another 26.0% (n=56/215). Women with severe hypertensive disorders of pregnancy had a preterm birth (<37 weeks) in 67.1% of the cases (n=143/215; adjusted odds ratio, 14.1; 95% confidence interval, 10.5-19.0), a baby with a low birthweight (<2500 g) in 62.2% of the cases (n=130/215; adjusted odds ratio, 10.8; 95% confidence interval, 8.1-14.5), and a baby with a low 5-minute Apgar score in 20.5% of the cases (n=43/215; adjusted odds ratio, 6.9; 95% confidence interval, 4.8-10.0). CONCLUSION: In Suriname, severe hypertensive disorders of pregnancy are strongly associated with adverse perinatal outcomes, with an increased risk for preterm birth, low birthweight, low Apgar score, and perinatal mortality. Prevention, early diagnosis, and management of hypertensive disorders of pregnancy are expected to reduce perinatal deaths substantially. Recommendations to reduce perinatal deaths in Suriname include the establishment of a national health plan for the management of severe hypertensive disorders of pregnancy and the introduction of perinatal death and neonatal near miss reviews.